2021
DOI: 10.1042/bsr20211658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serum irisin, neuregulin 4, and weight management on obese adolescent girls with polycystic ovary syndrome

Abstract: The study is aimed at investigating the association of serum irisin、Neuregulin 4 (NRG4), and Anti-müllerian hormone (AMH) with adolescent obesity with Polycystic ovary syndrome (PCOS) and the efficacy of weight management interventions. Serum levels of irisin, NRG4, AMH, sex steroid hormone, body mass index (BMI), serum insulin, and C-peptide were measured in 52 obese adolescent girls with PCOS (PCOS group) and 43 obese adolescent girls without PCOS (non-PCOS group). The levels of AMH, NRG4, serum irisin, sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Importantly, the relationship of NRG4 with insulin sensitivity remained significant after controlling for age, BMI, sex and hsCRP. In line with the current study, increased levels of serum NRG4 in insulin resistance-associated diseases, such as type 2 diabetes ( Kang et al, 2016 ; Chen et al, 2017a ; Kurek Eken et al, 2018 ; Wang et al, 2019c ; Kocak et al, 2019 ) and polycystic ovary syndrome ( Kurek Eken et al, 2019 ; Cao and Hu, 2021 ) have been reported. In contrast, a recent study described low levels of NRG4 in patients with type 2 diabetes in association to microalbuminuria ( Kocak et al, 2020 ), suggesting NRG4 as a putative marker of microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the relationship of NRG4 with insulin sensitivity remained significant after controlling for age, BMI, sex and hsCRP. In line with the current study, increased levels of serum NRG4 in insulin resistance-associated diseases, such as type 2 diabetes ( Kang et al, 2016 ; Chen et al, 2017a ; Kurek Eken et al, 2018 ; Wang et al, 2019c ; Kocak et al, 2019 ) and polycystic ovary syndrome ( Kurek Eken et al, 2019 ; Cao and Hu, 2021 ) have been reported. In contrast, a recent study described low levels of NRG4 in patients with type 2 diabetes in association to microalbuminuria ( Kocak et al, 2020 ), suggesting NRG4 as a putative marker of microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Others found reduced irisin levels in obese PCOS patients (13). Notably, serum irisin levels of obese PCOS women were signi cantly lower than those of non-obese PCOS patients (9,13). Behboudi-Gandevani et al (6) found that irisin has no association with BMI in women with or without PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circulating NRG4 was significantly associated with insulin resistance indicators, markers of obesity, and hormonal levels [ 139 ]. The most recent study investigating the impact of weight reduction on serum NRG4 levels in obese adolescent girls with PCOS [ 31 ] has also confirmed a higher initial NRG4 level in overweight patients [ 31 ]. In addition, the study showed that even a short (one-year-long) lifestyle intervention, including change of diet, increased physical activity and avoidance of sedentary behavior may enable to obtain NRG4 levels comparable to healthy control levels from the beginning of the study [ 31 ].…”
Section: Neuregulin-4mentioning
confidence: 94%
“…The aforementioned studies have emphasized the association of NRG4 with metabolic disorders: obesity seems to trigger secretion of NR4, and its high levels might be a form of adjustment to the low-grade chronic inflammation in PCOS; however, further research is required [ 31 , 137 , 139 ].…”
Section: Neuregulin-4mentioning
confidence: 99%